Piezoelectric and Electrically Conducting Filler-based Elastomer Composite For Piezoelectric Nano Generators - Kumar, Vineet; Alam, Md Najib; Park, Sang-Shin (Current Science, Engineering and Technology, 2025)
<span class=
Keywords: Piezoelectric nanogenerators